Reductive Amination Routes in the Synthesis of Piperidine IminoSugars. Issue 29 (14th April 2020) - Clemente, Francesca; Matassini, Camilla; Cardona, Francesca
Abstract : The reductive amination (RA) reaction plays a pivotal role in the synthesis of new C–N bonds, due to the availability of many different and low‐cost reagents and their operational simplicity. The introduction in a compound of a nitrogen‐containing moiety that can be reduced to an amine in the reaction medium allows to perform cascade reactions which further expand this method. The application of the intramolecular version of the RA to carbohydrates allows the synthesis of polyhydroxypiperidine iminosugars, which are among the most challenging and fascinating glycomimetics for a synthetic chemist. This minireview focuses on the use of RA and of the double reductive amination (DRA) reaction in the key ring‐closing step en route to the synthesis of these compounds. Abstract : Iminosugars are among the most fascinating glycomimetics. This Minireview highlights the efficiency of the intramolecular reductive amination (RA) strategy for the synthesis of piperidine iminosugar alkaloids starting from carbohydrate‐based precursors bearing different nitrogen‐containing functional groups.